A Scaling Scheme for DCT Precoded Optical Intensity-Modulated Direct Detection Systems. (29th November 2015) - Wang, Zhongpeng; Wang, Xiumin; Chen, Fangni; Qiu, Weiwei; Ye, Linpeng
Abstract : A scaling technique is employed to improve the performance of a Discrete Cosine Transform (DCT) precoded optical intensity-modulated direct detection (IM/DD) OFDM system, which fully exploits the dynamic range of a digital-to-analog converter (DAC). The theoretical analysis shows that the proposed scaling scheme can improve the BER performance of DCT precoded and scaled OFDM systems. The experiment results also show that the proposed scheme significantly improves the BER performance without changing the receiver structure. The measured received sensitivity at a BER of 10 −3 for a 4 G samples/s (2.7 Gbits/s) DCT precoded and scaled OFDM signal and after 100 km standard single-mode fiber (SMF) transmission has been improved by 3 and 1.3 dB when compared with the original OFDM system and conventional DCT precoded OFDM system, respectively.